Inclusion of students with ADA in school: a Review of Behaviorally-Based Research Intervention - Zappella, Emanuela (Formazione & insegnamento, 2017)
Student with autism spectrum disorders (ASDs) often have difficulties in social interaction skills, which may prevent their successful inclusion in school. This paper examines the possibility of using the ABA method for facilitating social interaction of these students in an inclusive environment. After presenting the characteristics